Effects of soluble surfactant on lateral migration of a bubble in a pressure driven channel flow. (May 2020) - Ahmed, Zaheer; Izbassarov, Daulet; Lu, Jiacai; Tryggvason, Gretar; Muradoglu, Metin; Tammisola, Outi
Highlights: Interface-resolved direct numerical simulations are performed. Effect of soluble surfactant on the lateral migration of a bubble is examined. Even a small amount of surfactant is sufficient to alter the direction of lateral migration. Surfactant triggers the path instability earlier and amplifies the oscillations afterwards. Abstract: The effects of soluble surfactant on the lateral migration of a bubble in a pressure-driven channel flow are examined by interface-resolved numerical simulations. The interfacial and bulk surfactant concentration evolution equations are solved fully coupled with the incompressible Navier-Stokes equations. A non-linear equation of state is used to relate interfacial surface tension to surfactant concentration at the interface. Extensive computations are performed to investigate the bubble dynamics for a wide range of parameters. It is found that surfactant dramatically changes the bubble dynamics. In the clean case, the bubble position depends on its deformability, characterized by the E o ¨ tv o ¨ s ( Eo ) and the capillary ( Ca ) numbers. The spherical bubble moves towards the wall, while the deformable one migrates away from it. On the other hand, in the presence of the surfactant, even the spherical bubble moves away from the wall. It is also found that the contaminated bubble stays away from the wall for Eo  ≤ 0.1 and Eo  ≥ 1.5 while it migrates towards the wall for 0.1 <  Eo  < 1.5. Also, at high Eo, the onset of path instability is observed for both the clean and the contaminated cases. However, adding surfactant to the system triggers the path instability earlier and amplifies the oscillations afterwards.